Brain Box - Adi Iskandar, Alisha Dafinah; Khairol Nizam, Nurul Farahani; Mardhiyyah Rohaizad, Nurul Ajiebah; Abdullah, Nurul Huda; Ku Shahril, Ku Syafiqah Arina; Akhyani, Nur Atiqah (2025)
In today’s diverse classroom environments, students exhibit a wide range of learning preferences and sensory modalities, yet traditional teaching methods remain predominantly auditory. This mismatch between teaching style and student learning preference has contributed to decreased engagement and concentration, especially in critical subject areas like STEM and languages. This project introduces Brain Box, an innovative educational tool designed to cater to multi-sensory learning styles—visual, auditory, reading/writing, and kinaesthetic—by providing targeted, interactive components that align with students’ sensory strengths. Brain box modules are visual learners from diagrams and color-coded flashcards, auditory learners from sound-based instructions, reading/writing learners from labeled texts and prompts, and kinaesthetic learners from hands-on activities and manipulatives. By integrating these elements into both STEM and language curricula, Brain Box supports deeper conceptual understanding and promotes active participation. The project also serves as a formative assessment tool for teachers. By tracking student responses and progress through Brain Box modules, educators can better identify which sensory methods resonate most with individual learners, enabling more personalized and effective instructional approaches. Early trials indicate improved focus, comprehension, and enthusiasm among students when multi-sensory strategies are employed. Ultimately, Brain Box not only addresses the issue of classroom distraction due to sensory mismatch but also empowers both students and educators by transforming passive learning environments into dynamic, inclusive spaces where all learning preferences are acknowledged and nurtured. This approach fosters greater equity in education, supporting diverse learners in reaching their academic potential.